The convergence of an implicit mean value iteration - B. E. Rhoades; Ştefan M. Şoltuz (International Journal of Mathematics and Mathematical Sciences)
We show the convergence of an implicit mean value iteration when applied to uniformly pseudocontractive maps. Remarks about other implicit mean value iterations are given.